2022
DOI: 10.3390/children9070998
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Dedicated Sedation Team on the Incidence of Complications in Pediatric Procedural Analgosedation

Abstract: The number of pediatric procedural sedations for diagnostic and minor therapeutic procedures performed outside the operating room has increased. Therefore, we established a specialized interdisciplinary team of pediatric anesthesiologists and intensivists (Children’s Analgosedation Team, CAST) at our tertiary-care university hospital and retrospectively analyzed the first year after implementation of the CAST. Within one year, 784 procedural sedations were performed by the CAST; 12.2% of the patients were infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Beyond standards for structural aspects of procedural sedation, qualification of sedation personnel has been shown to be one of the major contributors to patient safety [12,27,28].…”
Section: Qualification Of Sedation Teamsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond standards for structural aspects of procedural sedation, qualification of sedation personnel has been shown to be one of the major contributors to patient safety [12,27,28].…”
Section: Qualification Of Sedation Teamsmentioning
confidence: 99%
“…Numerous studies have identified significant risk factors for adverse events related to patient, sedation and procedure (Table 1) [9][10][11][12][13][14]. Adverse events require immediate and competent management, but ideally they are anticipated, and appropriate measures are adopted proactively.…”
Section: Adverse Events In Paediatric Procedural Sedationmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying attributes and their levels is the most important step to ensure the validity of the DCE (29). In this study, the attributes and their levels were specified using literature reviews (15,23,(30)(31)(32)(33)(34)(35)(36), interviews with parents of pediatric dental patients, and expert consultation. Thus, the DCE used in our study included 6 attributes recorded at 3 or 4 levels.…”
Section: Identification Of Attributes and Levelsmentioning
confidence: 99%
“…With the concept of comfortable medical treatment, pediatric sedation is steadily developing for a growing number of non-invasive and painless examinations, such as CT, MRI, echocardiography, electroencephalogram and lung function. Meanwhile, the rapid growth of medical units for pediatric procedural sedation in China, and the widely ranged use of drugs and techniques in pediatric sedation, have resulted in a significant difference between sedation levels, effectiveness and associated risks [4]. Some studies have reported the sedation-related adverse event rates ranging from 6.5% to 22.02% [4][5][6].…”
Section: Introductionmentioning
confidence: 99%